The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3758/s13414-015-0944-z
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic remapping of object-selective information

Abstract: Saccadic remapping, a presaccadic increase in neural activity when a saccade is about to bring an object into a neuron’s receptive field, may be crucial for our perception of a stable world. Studies of perception and saccadic remapping, like ours, focus on the presaccadic acquisition of information from the saccade target, with no direct reference to underlying physiology. While information is known to be acquired prior to a saccade, it is unclear whether object-selective or feature-specific information is rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 62 publications
3
20
0
Order By: Relevance
“…This hypothesis was further supported by several subsequent studies (Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015). However, in recent years a number of studies have provided evidence that feature information, in addition to attentional pointers, is also involved in transsaccadic remapping (Cha & Chong, 2013;Demeyer, De Graef, Wagemans, & Verfaillie, 2009, 2010Demeyer, Graef, Verfaillie, & Wagemans, 2011;Eccelpoel, Germeys, Graef, & Verfaillie, 2008;Edwards, VanRullen, & Cavanagh, 2017;Fracasso, Caramazza, & Melcher, 2010;Gordon, Vollmer, & Frankl, 2008;Habtegiorgis, Rifai, Lappe, & Wahl, 2018;Harrison & Bex, 2014;Hayhoe, Lachter, & Feldman, 1991;He et al, 2017;Herwig & Schneider, 2014;Koller & Rafal, 2018;Melcher, 2007;Nakashima & Sugita, 2017;Oostwoud Wijdenes, Marshall, & Bays, 2015;Paeye, Collins, & Cavanagh, 2017;Prime, Niemeier, & Crawford, 2006;Prime, Vesia, & Crawford, 2011;Sligte et al, 2017;Wittenberg, Bremmer, & Wachtler, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013;Zimmermann et al, 2017;Zimmermann, Weidner, Abdollahi, & Fink, 2016;Zirnsak et al, 2011). Our study is in line with these studies, and further...…”
Section: Remapping Of Features or Attentional Pointers?supporting
confidence: 92%
“…This hypothesis was further supported by several subsequent studies (Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015). However, in recent years a number of studies have provided evidence that feature information, in addition to attentional pointers, is also involved in transsaccadic remapping (Cha & Chong, 2013;Demeyer, De Graef, Wagemans, & Verfaillie, 2009, 2010Demeyer, Graef, Verfaillie, & Wagemans, 2011;Eccelpoel, Germeys, Graef, & Verfaillie, 2008;Edwards, VanRullen, & Cavanagh, 2017;Fracasso, Caramazza, & Melcher, 2010;Gordon, Vollmer, & Frankl, 2008;Habtegiorgis, Rifai, Lappe, & Wahl, 2018;Harrison & Bex, 2014;Hayhoe, Lachter, & Feldman, 1991;He et al, 2017;Herwig & Schneider, 2014;Koller & Rafal, 2018;Melcher, 2007;Nakashima & Sugita, 2017;Oostwoud Wijdenes, Marshall, & Bays, 2015;Paeye, Collins, & Cavanagh, 2017;Prime, Niemeier, & Crawford, 2006;Prime, Vesia, & Crawford, 2011;Sligte et al, 2017;Wittenberg, Bremmer, & Wachtler, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013;Zimmermann et al, 2017;Zimmermann, Weidner, Abdollahi, & Fink, 2016;Zirnsak et al, 2011). Our study is in line with these studies, and further...…”
Section: Remapping Of Features or Attentional Pointers?supporting
confidence: 92%
“…Conventionally, the visual field is characterised by three regions, going from the centre to the periphery of the retina: (1) the fovea, which subtends a visual angle of 1°eccentricity and is responsible for high resolution vision; (2) the parafovea, which stretches out to 4-5°; and (3) the periphery, which extends beyond the parafovea and cover the rest of the visual field (see Larson & Loschky, 2009 for provising a brief summary in the context of scene gist recognition). Although the visual acuity strongly decreases in the parafovea and in the periphery, i.e., in extra-foveal vision (e.g., Strasburger, Rentschler, & Jüttner, 2011), the area of the visual field from which observers can accrue useful information is quite large (see Rayner, 2014;Rosenholtz, 2016;B. Wolfe, Dobres, Rosenholtz, & Reimer, 2017, for reviews) and it can roughly corresponds to 8°in each direction from fixation for visual search in naturalistic scenes (Nuthmann, 2013).…”
mentioning
confidence: 99%
“…They demonstrated that the visual system predictively integrates motion signals between the current and the postsaccadic retinotopic location during the period of saccade preparation. Finally, also higher level features as facial expressions are remapped across saccades (Melcher, 2005;Wolfe & Whitney, 2015). All these studies suggest that transsaccadic remapping takes into account visual feature information rather than shifting only abstract position information.…”
Section: Discussionmentioning
confidence: 92%